TINJAUAN TERHADAP KEPEMILIKAN TANAH SECARA GUNTAI (ABSENTEE) DI DESA GIRISAKO KECAMATAN LOGAS TANAH DARAT BERDASARKAN PERATURAN PEMERINTAH NOMOR 224 TAHUN 1961 JO PERATURAN PEMERINTAH NOMOR 41 TAHUN 1964 TENTANG PELAKSANAAN PEMBAGIAN TANAH DAN PEMBERIAN GANTI KERUGIAN - Mayangsari, Lili Tampi; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Land is an important resource for the society, both as planting media, and asspace or place to conduct various activities. As an implementation of Law Number 5 Year 1960 on the Basic Regulation of Agrarian Principles (UUPA) the Government issued Law No. 56 Prp Year 1960 on the Stipulation on the Area of Farmland with the implementation of Government Regulation No. 224 Year 1961 on the Implementation of Land Distribution and the Provision of Compensation, in Article 3 paragraph (1) of Government Regulation No. 224 Year 1961 in conjunction with Article 1 of Government Regulation No. 41 Year 1964 there is a prohibition for “Absentee/Guntai land ownership which states that the ownership of farmland by a person who resides outside the sub-district where the land is located is prohibited in order that the farmers can be active and effective in working on their farmland, so that their productivity can be more optimized. In reality, there are still many people who own farmland by “absentee/guntai ownership “ In Girisako Village, Logas Tanah Darat District, therefore, in practice the existence of the regulation on the prohibition of “absentee/guntai” land ownership has not been able to be applied effectively. The purpose of writing this : First, to know about the implementation of land ownership of the guntai (absentee) in the Village Girisako, Logas Tanah Darat District. Second, to determine the legal consequences of not running Government Regulation No. 224 Year 1961 in conjunction with of Government Regulation No. 41 Year 1964 on the Implementation of Land Distribution and Compensation in the Village Girisako Logas Tanah Darat District.This study uses the method of Sociological Juridical, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Girisako Village Kecamtan Logas Tanah Darat Kuantan Singingi Regency, while the population and sample are all parties related to the problems studied in this research, data source used, primary data, secondary data and tertiary data, data collection technique in research this is by observation, interview and literature study.From the results of research problems there are two main things that can be concluded. Firstly, the Implementation of Government Regulation No. 224/1961 on Government Regulation No. 41/1964 concerning the prohibition of absentee land ownership in Girisako Village, that there is still absentee land ownership which has actually occupied the farm after years and this is not in accordance with what is desired by PP No . 224 of 1961 jo PP No. 41 of 1964 and UUPA. Secondly, the legal consequences of the absence of PP. 224 Year 1961 Jo PP No. 41 year 1964 absentee landowners must transfer their land rights to people residing in Girisako Village or to be forcibly taken by the government to be redistributed according to Landreform Program.Keyword: Farmland, Guntai/Absentee